2013
DOI: 10.1111/his.12095
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical evaluation of the proteins Wnt1 and glycogen synthase kinase (GSK)‐3β in invasive breast carcinomas

Abstract: Wnt1 expression in the invasive tumour cells seems to promote differentiation and apoptosis, while being related inversely to proliferation. Therefore, this suggests its participation in the primary stages of breast carcinogenesis. The latter is supported further by the immunodetection of Wnt1 in in-situ carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…These results confirm that Wnt1 is up-regulated in breast cancer, and that it is not involved with a more invasive breast tumour type; both findings confirming those of previous studies [9][10][11]21,22]. EpithelialCatenin and sFRP4 revealed no significant difference between tumour types and also between normal and tumour tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results confirm that Wnt1 is up-regulated in breast cancer, and that it is not involved with a more invasive breast tumour type; both findings confirming those of previous studies [9][10][11]21,22]. EpithelialCatenin and sFRP4 revealed no significant difference between tumour types and also between normal and tumour tissue.…”
Section: Discussionsupporting
confidence: 89%
“…It is well established that Wnt1 is involved in breast cancer [9][10][11]; however, this study has revealed that Wnt1 expression does not differ with breast cancer invasiveness, showing that Wnt1 plays a role in a breast tumour phenotype but not with a more advanced disease state, which is in agreement with Karim et al [21] who found that, while cytoplasmic Wnt1 expression increased with increasing tumour grade, it was not a statistically significant difference. Indeed, a more recent study [22] reported that Wnt1 is only involved in the initial phases of breast cancer development, where it supports differentiation and apoptosis of the tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the institutional ethical committee of the Medical School of the University of Athens. Informed consent was signed by all patients under study in order to use for research purposes their biological samples and clinical data [27].…”
Section: Methodsmentioning
confidence: 99%
“…At the time of the last follow-up, 25 (20.7%) patients had died from disease, 15 (12.4%) were alive with disease and 81 (66.9%) were alive and disease-free. All patients received conventional postoperative treatment depending on the extent of the disease, including adjuvant chemotherapy, radiation therapy and anti-estrogen therapy, when indicated, according to the consensus recommendations at the time [35]. [19,36].…”
Section: Patientsmentioning
confidence: 99%